Load Capacity and the Stress-stain State of the Poly Eccentric Connections with Interference. (2016) - Chukhlantsev, Evgeny; Schenyatskiy, Alexey
Abstract: The article provides an overview of the poly contact connections with a tightness. The range of their application, considered the advantages and disadvantages. The methods of calculating the load capacity and the stress - strain state under different conditions of contact interaction. Numerical simulations of the poly contact connection with interference for different relative positions of the three mating parts. The analysis of the load-bearing capacity and stress - strain state to the extreme positions of the connection details. Obtained geometric load capacity depending on the angles of rotation of mating parts which can significantly speed up the calculations. Spend a full-scale experiment, whose results confirm the adequacy of the mathematical model. At the end of the article presents the findings.